Pedestrian profile and perception of walkability in Hêvié, Ouèdo, and Togba in Abomey Calavi, Republic of Benin in West Africa - KADJA, Cossi Jeannot Melchior; DANDONOUGBO, Iléri; KOREM, Ayira; ALLAGBE, Benjamin Sotondji (Edelweiss Applied Science and Technology, 2025)
The positive perception of walkability ensures more frequent and continuous use compared to a high objective level of walkability. In a context of increasing traffic-related air pollution, it is important to find alternatives to motorized transport, at least for short distances. This issue is even more important in peri-urban areas, where distances are long and roads are poorly designed. Pedestrian profiles also play a key role in the perception of walkability. The present study examines the perception of walkability and assesses its relationship with the profile of peri-urban dwellers in the Republic of Benin, in the Hêvié, Ouèdo, and Togba districts of the Abomey-Calavi municipality. To this end, the Neighborhood Environment Walkability Scale - Abbreviated (NEWS-A) questionnaire was adapted, and 117 pedestrians randomly selected in the study area were questioned between October 6 and 10, 2024, at different times of the day. The data processing allows us to understand that the perception of walkability is evaluated through six criteria: Aesthetics/attractiveness, Access, Comfort, Safety, Connectivity, and Inclusivity. In addition, pedestrians generally have a poor perception of walkability. Pedestrians’ gender significantly influences their perception of aesthetics/attractiveness, comfort, and connectivity. In parallel, income significantly correlates with perceptions of accessibility, comfort, and connectivity.